ANALISIS PEMETAAN FAKTOR RESIKO KEJADIAN STUNTING MENGGUNAKAN APLIKASI GIS DI KABUPATEN PASAMAN - Rahmi Kurnia Gustin; Tika Ramadanti; Dina Ediana; Agia Sepneta Putra (HUMAN CARE JOURNAL, 2023)
Based on Riskesdas data for 2013, in Indonesia there are 37.2% of children under five are stunted. Stunting is the cause of 2.2 million of all causes of under-five deaths in the world. The prevalence of stunting in 2020 in Pasaman Regency is 19.1% with rank number 3 out of 19 Regencies/Cities of West Sumatra. The purpose of this study was to describe the incidence of stunting and factors for stunting in Pasaman Regency in 2021. The research method is a quantitative descriptive with a cross-sectional design and utilizes GIS applications. The research population was 12 Districts of Pasaman Regency in 2021. The research samples were Lansat Kadap and Lubuk Attitude, during the research from July to August 2021, the research locations were in Lansat Kadap and Lubuk Attitudeing Districts. The results of the study illustrate that the prevalence of stunting in children under five in the Lansat Kadap area is 36.9%, while Lubuk Attitude is 6.2%. The risk factors in Lansat Kadap District are the percentage of LBW 3.3%, Coverage of Posyandu Presence 57.5%, Quality drinking water sanitation 65.8%, Coverage of Exclusive Breastfeeding 89.1%. The risk factors in Lubuk Attitudeing District are the percentage of LBW 2.0%, Coverage of Posyandu Presence 65.8%, Quality drinking water sanitation 88.7%, Coverage of Exclusive Breastfeeding 88.9%. Based on the risk factors in the Lansat Kadap and LubukACTing areas, those that have met the target are the percentage of LBW and the coverage of exclusive breastfeeding, while those that have not met the target are the coverage of posyandu attendance and quality drinking water sanitation.